Bridging Law, Technology, and Justice in the Digital Ag - Al-Farjani, Saleh Hashem; Alazhari, Waheed (INDONESIAN JOURNAL OF SUSTAINABILITY, 2026)
Abstract Digital innovation has emerged as a powerful force reshaping legal systems, governance mechanisms, and the protection of human rights worldwide. Technologies such as artificial intelligence, digital platforms, algorithmic governance, and big data have accelerated legal reform while simultaneously creating new challenges related to inequality, surveillance, and the concentration of unaccountable power. This article explores the nexus between digital innovation, legal reform, and social justice through an interdisciplinary legal approach that combines doctrinal legal analysis with human rights theory, political economy, and ethical perspectives. Employing a qualitative normative methodology based on secondary legal and scholarly sources, the study examines contemporary legal responses to digital transformation and assesses their effectiveness in safeguarding human dignity, equality, and accountability. The analysis reveals that although digital technologies enhance access to information and justice for certain groups, they also exacerbate structural exclusion, algorithmic bias, labor precarity, and transnational regulatory fragmentation. The findings further indicate that legal regulation alone is insufficient to govern digital power in the absence of ethical foundations, integrated social policy, and coordinated global legal frameworks. The study concludes that without a justice-oriented regulatory paradigm, digital legal reform risks reinforcing technocratic domination rather than achieving inclusive and equitable modernization. Accordingly, the article advocates for a human rights–centered, interdisciplinary model of digital governance that places social justice, accountability, and human dignity at the heart of future legal reform.Keywords: Digital innovation, Legal reform, Human rights, Social justice, Digital governance